End-user development - Raković Lazar; Sakal Marton; Pavlićević Veselin (Anali Ekonomskog fakulteta u Subotici, 2016)
Development and proliferation of graphical user interface and interactive software environments significantly contributed to the already present trend of end-user application development, which enables endusers who are not IT professionals to build applications and adjust software products to their needs up to a certain extent. According to some estimates, one third of business data generated in 2014 originated from applications developed by end-users. This paper examines the reasons that stimulate end-user application development, lists its potential benefits and introduces a delineation between specific categories of end-users.